Toward a Holistic Planning Culture Framework: Integrating Individual, Collective, and Societal Dimensions - Perić, Ana (Global Journal of Cultural Studies, 2025)
Planning culture scholarship has evolved significantly over six decades, yet fundamental analytical tensions persist: between systematic comparison and contextual specificity, between structural determinism and agential capacity, and between cultural continuity and institutional change. Existing frameworks, particularly the influential Culturised Planning Model, struggle to address these tensions because they inadvertently reproduce the structure-agency dualism they seek to transcend, treating institutional contexts as relatively fixed parameters that shape but are not shaped by planning practice. This paper presents a holistic planning culture framework that bridges this divide by drawing on sociological institutionalism’s insights into how actors simultaneously work within, reshape, and transform institutional arrangements. The framework distinguishes three interdependent cultural layers: individual attitudes (encompassing knowledge, beliefs, and actions), collective practices (including procedural rules and actors’ constellations), and societal environment (reflected in steering styles). Unlike hierarchical models that imply unidirectional causation, this framework conceptualises these layers as mutually constitutive – simultaneously structuring and being structured by planning practice. This recursive character explains both cultural reproduction (through mutually reinforcing relationships) and transformation (through contradictions creating openings for institutional entrepreneurship). The framework enables more nuanced analysis of how planning cultures operate across multiple scales, how identical formal instruments produce divergent outcomes, and how endogenous change emerges through everyday planning practice. By treating planning culture as a dynamic institutional field rather than a static context, the framework supports more reflexive, culturally-informed planning practice.